(untitled) (Research, Society and Development, 2022)
The adaptation of the environment to human needs alters the natural configuration of landscapes over the years, reflecting the forms of land use and occupation. The processes of use and occupation inherent to the configuration of landscapes are concomitant, since the outbreak of the first process (use) alters the panorama of the second (occupation). In this sense, human actions on the environment are at the center of this problem. In the Brazilian semiarid region, the process of land use and occupation is influenced by traditional practices peculiar to that region, such as rainfed agriculture and traditional livestock farming. In order to evaluate the influence of these practices on the space-time configuration of landscapes, this work aimed to analyze the space-time dynamics of land use and occupation in the municipality of Condado-PB, from 1989 to 2018, through the Soil Adjusted Vegetation Index (IVAS). This remote sensing technique allowed the elaboration and analysis of maps of land use and occupation through the digital processing of images from the Landsat 5 – TM and Landsat 8 – OLI satellites. Five classes of use and occupation were identified, with the vegetation classified as arboreal, shrubby and grassy (or herbaceous), in addition to exposed soil and water bodies. The results showed an increase in the classes of arboreal vegetation (105.44%), grass/herbaceous (386.96%) and water bodies (179.33%). Shrub vegetation and exposed soil decreased by 2.92% and 62.6% respectively. Overall, vegetation grew in occupied area from 44.9% in 1989 to 70.9% in 2018.